New Frontiers in Stellar Interferometry 2004
DOI: 10.1117/12.552979
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive DFT-based fringe tracking and prediction at IOTA

Abstract: An automatic fringe tracking system has been developed and implemented at the Infrared Optical Telescope Array (IOTA). In testing during May 2002, the system successfully minimized the optical path differences (OPDs) for all three baselines at IOTA. Based on sliding window discrete Fourier transform (DFT) calculations that were optimized for computational efficiency and robustness to atmospheric disturbances, the algorithm has also been tested extensively on off-line data. Implemented in ANSI C on the 266 MHz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…What are really wanted are the expected position of the next interferogram and the confidence of that expectation. Although the improvement is expected to be slight, the linear proof of concept [4] shows measurable predictability of the fringe motion, even with a 3 Hz scan frequency (would be more predictable with faster scanning). The linear tests also indicate that the jump variance may be somewhat predictable-this could be incorporated into the exponential weighting function.…”
Section: Potential Algorithm Improvementsmentioning
confidence: 93%
See 2 more Smart Citations
“…What are really wanted are the expected position of the next interferogram and the confidence of that expectation. Although the improvement is expected to be slight, the linear proof of concept [4] shows measurable predictability of the fringe motion, even with a 3 Hz scan frequency (would be more predictable with faster scanning). The linear tests also indicate that the jump variance may be somewhat predictable-this could be incorporated into the exponential weighting function.…”
Section: Potential Algorithm Improvementsmentioning
confidence: 93%
“…Gradient-based optimization, motion prediction, and other offline analyses are discussed in [4]. As compared to that publication, the present article uses data from 2004 and focuses on the adaptive DFT-based tracking algorithm, whereas [4] focuses on the IOTA implementation issues, envelope-based tracking, and offline gradient-based optimization of all packet parameters.…”
Section: Related Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…This paper reviews progress in science and technology at the Infrared Optical Telescope Array (IOTA), since the last such review, 1 some of which is reported in the present volume. 2,3,4,5,6 Briefly, IOTA is a long-baseline optical interferometer located at the Smithsonian Institution's Whipple Observatory on Mount Hopkins, AZ. It comprises three 45-cm diameter telescopes which can be positioned at 17 stations on an L-shaped track, where the arm lengths are 15 m toward the south-east and 35 m toward the north-east.…”
Section: Introductionmentioning
confidence: 99%
“…There are obviously many other ways to estimate x GD from a set of data, but we assume that this is a second order problem. Indeed, Pedretti et al (2004) compared three different algorithms to estimate the group delay with a temporal method and noted only little differences in the performance, even with an algorithm as sophisticated as the one proposed by Wilson et al (2004).…”
Section: Description Of the Simulationsmentioning
confidence: 99%